2020
DOI: 10.21079/11681/37574
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific case studies for determining ground snow loads in the United States : case study spreadsheet

Abstract: The U.S. Army Cold Regions Research and Engineering Laboratory (CRREL) has mapped ground snow loads for much of the United States. In some areas where extreme local variations preclude mapping on a national scale, instead of loads, "CS" is used to indicate that Case Studies are needed. This report and the accompanying spreadsheet, which contains the 15,104-station CRREL ground snow load database, provide the information needed to conduct Case Studies. When the latitude, longitude, and elevation of a site of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The block maxima approach uses zero-inflated probability distributions to account for the fact that some locations have annual maximum snow loads of zero in certain years. With that in mind, we observed that accounting for zero-inflated snow years using precedence set by Buska et al (2020) had a negligible effect on the MRI estimates. Across the different station types (i.e., FOS, COOP, and SNOTEL), we can see that the traditional block maxima (BM), the mean-adjusted gamma (GMA), and POT Bayesian (BAYES) approach tend to be closer to the reference line of 1, which represents values that equal the median of the six approaches.…”
Section: Short-term Design Snow Load Estimatesmentioning
confidence: 87%
“…The block maxima approach uses zero-inflated probability distributions to account for the fact that some locations have annual maximum snow loads of zero in certain years. With that in mind, we observed that accounting for zero-inflated snow years using precedence set by Buska et al (2020) had a negligible effect on the MRI estimates. Across the different station types (i.e., FOS, COOP, and SNOTEL), we can see that the traditional block maxima (BM), the mean-adjusted gamma (GMA), and POT Bayesian (BAYES) approach tend to be closer to the reference line of 1, which represents values that equal the median of the six approaches.…”
Section: Short-term Design Snow Load Estimatesmentioning
confidence: 87%
“…These circumstances must be considered in the design of drainage and siphon systems of high-rise and low-rise buildings [3,4]. On warm roofs, runoff meltwater can flow into the building, and the cold eaves arrive and freeze on it [5]. At the edge of a roof, accumulating ice creates a barrier to melting snow, allowing it to accumulate and, in some cases, causing sections of the roof to collapse [6].…”
Section: Introductionmentioning
confidence: 99%